Analisis Perkembangan Nilai Agama dan Moral Pendidikan Anak Usia Dini di Pondok Pesantren Ibnul Fallaah Bangsal Pampangan Ogan Komering Ilir - Rizki Novia Rosa; Mardeli; Elsa Cindrye (CV. Ulil Albab Corp, 2022)
This research aim to Analysis of the Development of Religious and Moral Values ​​in Early Childhood Education at the Ibnul Fallaah Islamic Boarding School, Bangsal Village, Pampangan District, Ogan Komering Ilir Regency. The type of research used in this research is field research. The purpose of this study was to analyze the development of religious and moral values ​​of early childhood education in Ibnul Fallaah Early Childhood Education, Bangsal Village, Pampangan District, Ogan Komering Ilir Regency. In this study, through habituation and culture from Islamic boarding schools as well as Islamic boarding schools activities can help teachers in developing religious and moral values ​​for early childhood in PAUD Ibnul Fallaah, Bangsal village, Pampangan district, Ogan Komering Ilir district. In terms of moral development, children can imitate the attitude, perspective, sense of responsibility and politeness taught by the teacher. Regarding religious activities, children can do well according to what the teacher teaches, such as daily prayer, ablution movements, reciting the Koran and prayer movements.